2016
DOI: 10.1002/prp2.246
|View full text |Cite
|
Sign up to set email alerts
|

A novel thiophene‐3‐carboxamide analog of annonaceous acetogenin exhibits antitumor activity via inhibition of mitochondrial complex I

Abstract: Previously we synthesized JCI‐20679, a novel thiophene‐3‐carboxamide analog of annonaceous acetogenins which have shown potent antitumor activity, with no serious side effects, in mouse xenograft models. In this study, we investigated the antitumor mechanism of JCI‐20679. The growth inhibition profile (termed “fingerprint”) of this agent across a panel of 39 human cancer cell lines (termed “JFCR39”) was measured; this fingerprint was analyzed by the COMPARE algorithm utilizing the entire drug sensitivity datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…So as to investigate whether Mubritinib indeed behaves as an ETC inhibitor in AML cells, we compared the inhibition pattern induced by Mubritinib treatment with that of known ETC inhibitors (Deguelin (complex I), 47,48 and Oligomycin (complex V)) for 56 primary AML samples (see patient characteristics in Supplementary Table S7). We found that the two ETC inhibitors’ inhibitory patterns are highly similar to that of Mubritinib (r=0.9, p<0.0001 for Deguelin, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…So as to investigate whether Mubritinib indeed behaves as an ETC inhibitor in AML cells, we compared the inhibition pattern induced by Mubritinib treatment with that of known ETC inhibitors (Deguelin (complex I), 47,48 and Oligomycin (complex V)) for 56 primary AML samples (see patient characteristics in Supplementary Table S7). We found that the two ETC inhibitors’ inhibitory patterns are highly similar to that of Mubritinib (r=0.9, p<0.0001 for Deguelin, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In Guadeloupe (French West Indies) there is an unusually high incidence of atypical parkinsonism, which has been linked to regular consumption of these plants, in particular soursop (Lannuzel et al, 2003(Lannuzel et al, , 2007(Lannuzel et al, , 2008. The thiophene-3-carboxamide analog of annonaceous acetogenins JCI-20679 inhibited the oxygen consumption of human non-small cell lung carcinoma NCI-H23 cells with a half maximal inhibitory concentration (IC 50 ) of 170 nM (Akatsuka et al, 2016). The acetogenin bullatacin, or rolliniastatin-2, inhibits respiration in insect-derived Sf9 cells.…”
Section: Rolliniastatin-1mentioning
confidence: 99%
“…The thiophene skeleton of APTM is widely used as a building block in many drugs with various pharmacological activities (Mishra et al , 2011 ; Gramec et al , 2014 ). Thiophene derivatives exhibit a broad spectrum of anticancer activities (Akatsuka et al , 2016 ; Abdallah et al , 2017 ; Mohareb et al , 2017 ; Unver and Canturk, 2017 ).…”
Section: Discussionmentioning
confidence: 99%